Research on the Coordination of Repeaters Distribution Based on CTCSS - Zhangquan Wang (Institute of Advanced Engineering and Science, 2014)
Applying repeaters and CTCSS for frequency transmission will beeasier. But how to arrange the repeaters to cover the areas and allocate the CTCSS is one of the most indispensable problems. At first, this paperestablishes the model to cover the area. According to previous study, ourapproach is to tile the region with hexagons inscribed within circles of radiusequal to the distance a user’s signal will reach effectively. Then, this paperchecks the repeaters’ usage loads whether the number of them is adequate forlarge number of users. This paper set five conditions which must be satisfied.And then report the 2 meter band which is close to the information that topichas given. This algorithm is to arrange the frequency division and allocate theCTCSS step by step.